Jak to zrobić? Zadanie w załączniku.
![Jak To Zrobić Zadanie W Załączniku class=](https://pl-static.z-dn.net/files/d68/b1568792a174786485fded1379e90103.jpg)
Odpowiedź:
a) [tex]\frac{4\sqrt{0,72}-3\sqrt{4,5}+4,6\sqrt{2} }{-5\sqrt{1,5} +0,3\sqrt{6}-2\sqrt{x} 0,96 }= \frac{4\sqrt{\frac{18}{25} }-3\sqrt{\frac{9}{2} } +\frac{23}{5}\sqrt{2} }{-5\sqrt{\frac{3}{2} }+\frac{3}{10} \sqrt{6}-2\sqrt{\frac{24}{25} } } =\frac{4\frac{\sqrt{18} }{5} -3\frac{3}{\sqrt{2} }+\frac{23}{5}\sqrt{2} }{-5\frac{\sqrt{3} }{\sqrt{2} } +\frac{3}{10} \sqrt{6}-2\frac{\sqrt{24}}{5} } =[/tex][tex]\frac{\frac{12\sqrt{2} }{5} -\frac{9\sqrt{2} }{{2} }+\frac{23\sqrt{2}}{5} }{-\frac{5\sqrt{6} }{{2} } +\frac{3\sqrt{6}}{10}-\frac{4\sqrt{6}}{5} }=[/tex][tex]\frac{\frac{24\sqrt{2} }{10} -\frac{45\sqrt{2} }{{10} }+\frac{46\sqrt{2}}{10} }{-\frac{25\sqrt{6} }{{10} } +\frac{3\sqrt{6}}{10}-\frac{8\sqrt{6}}{10} }=\frac{\frac{25\sqrt{2} }{10} }{-\frac{30\sqrt{6} }{10} } =\frac{\frac{5\sqrt{2} }{2} }{-3\sqrt{6} } =\frac{\frac{5\sqrt{12} }{2} }{-3*6} =\frac{\frac{5*2\sqrt{3} }{2} }{-18} =-\frac{5\sqrt{3} }{18}[/tex]
b) [tex]\frac{-10\sqrt[3]{0,192}-1\frac{4}{5}\sqrt[3]{3}+5,6\sqrt[3]{\frac{3}{8} } }{5\sqrt[3]{0,054}-4,5\sqrt[3]{\frac{2}{125} } } =[/tex][tex]\frac{-10\sqrt[3]{\frac{24}{125} }-\frac{9}{5}\sqrt[3]{3}+\frac{28}{5} \sqrt[3]{\frac{3}{8} } }{5\sqrt[3]{\frac{27}{500} }-\frac{9}{2} \sqrt[3]{\frac{2}{125} } } =[/tex][tex]\frac{-10*\frac{2\sqrt[3]{3} }{5} -\frac{9\sqrt[3]{3}}{5}+\frac{28}{5} *{\frac{\sqrt[3]{3}}{2} } }{5*{\frac{3}{5\sqrt[3]{4} } }-\frac{9}{2}* {\frac{\sqrt[3]{2} }{5} } } =[/tex][tex]\frac{{4\sqrt[3]{3} }{} -\frac{9\sqrt[3]{3}}{5}+{\frac{14\sqrt[3]{3}}{5} } \\ }{{\frac{3}{\sqrt[3]{4} } }-{\frac{9\sqrt[3]{2} }{10} } } =\frac{-3\sqrt[3]{3} }{\frac{3\sqrt[3]{2} }{2} -\frac{9\sqrt[3]{2} }{10}}=\frac{-3\sqrt[3]{3} }{\frac{3\sqrt[3]{2} }{5} } ={-3\sqrt[3]{3} *\frac{5}{3\sqrt[3]{2}}=-\frac{5\sqrt[3]{3} }{\sqrt[3]{2} } =-\frac{5\sqrt[3]{12} }{2}[/tex]
c)[tex]\frac{8\sqrt{2,45}-1,2 \sqrt{\frac{5}{9}}-2,25\sqrt{ 3\frac{77}{81} } }{5\sqrt{3,63}-17\frac{1}{2}\sqrt{\frac{3}{49} } } =[/tex][tex]\frac{8\sqrt{\frac{49}{20} }-\frac{6}{5} \sqrt{\frac{5}{9}}-\frac{9}{4} \sqrt{ \frac{320}{81} } }{5\sqrt{\frac{363}{100} }-\frac{35}{2}\sqrt{\frac{3}{49} } } =\frac{8*\frac{7}{2\sqrt{5} }-\frac{6}{5} *\frac{\sqrt{ 5}}{3}-\frac{9}{4}*\frac{8\sqrt{5} }{9} }{5*\frac{11\sqrt{3} }{10} -\frac{35}{2}*\frac{\sqrt{3} }{7} }[/tex][tex]\frac{4*\frac{7}{\sqrt{5} }-\frac{2}{5} *\sqrt{ 5}-{2\sqrt{5} } }{\frac{11\sqrt{3} }{2} -\frac{5}{2}*\sqrt{3} } } =[/tex][tex]\frac{\frac{28\sqrt{5} }{5 }-\frac{2\sqrt{ 5}}{5} -{2\sqrt{5} } }{\frac{11\sqrt{3} }{2} -\frac{5\sqrt{3} }{2} }=\frac{\frac{16\sqrt{5} }{5} }{3\sqrt{3} } =\frac{\frac{16\sqrt{15} }{5} }{9}=\frac{16\sqrt{15} }{5} *\frac{1}{9} =\frac{16\sqrt{15} }{45}[/tex]